Incentivos contributivos e inversión privada en Puerto Rico (2010)
This paper expects to show how the impositive taxes reduction that have been given to Puerto Rico’s businessman and investors has not contributed with the economic growth, also expects to explain how this policy has not supported the economic vulnerable sectors and has not generated new work’s business opportunities for people who really need it and for the progress of the society. In the last years people like foreign investors have been taken this social benefit for creating enterprises and for earning money, in the beginning of the policy’s promotion was a really good strategy for the country but later the money who all the companies constantly was being produced started to disappear and the country suffered an important fiscal crisis. A fact thaht could be avoided an now is a critical problem for the government and for the country’s budget.